KEBIJAKAN PENGKARYAAN KEMBALI PEKERJA SENIOR JEPANG PASCA PENSIUN (SUDUT PANDANG PERUSAHAAN MANUFAKTUR) - Dewi Saraswati Sakariah (IZUMI, 2015)
This study discusses about the phenomenon of the re-employed senior workers after retirement in Japan’s manufacturing companies. Japan is a country with the fastest aging population in the world that has many problems in itspopulation demographic.Meanwhile, the government launched intensifying efforts to make Japan rises from its economic recession since the 1990s.One of the efforts is call on each of the people who is still able to work to contribute to the employment sector in order to achieve economic growth strategy.One of the encouraged groups isthe post-retirementsenior workers in Japan’s manufacturing companies.The call on was well received while a number of companies were adopting this system with several different reasonsnamely life expectancy increases, the government calls to the people, the needs of the company's senior workers for productivity and skill transfering, the salary and the company's view of the young workers. This research will be interpreted by sosial changes perspective in society from Anthony Giidens. This study concludes that the phenomenon of the re-employed senior workers after retirement is the result of social changes that has occurred in Japanese society today.